Addressing the Reproducibility of Photocatalytic Carbon Dioxide Reduction. Issue 6 (16th March 2020) - Marx, Maximilian; Mele, Andrea; Spannenberg, Anke; Steinlechner, Christoph; Junge, Henrik; Schollhammer, Philippe; Beller, Matthias
Abstract: The front cover artwork for Issue 06/2020 is provided by Matthias Beller and co‐workers from the Leibniz Institute for Catalysis at the University of Rostock (Germany) and the University of Brest (France). The image shows the reproducibility problems with vastly varying turnover numbers that can arise when developing novel systems for photocatalytic transformations, such as carbon dioxide reduction. See the Full Paper itself at https://doi.org/10.1002/cctc.201901686 . Abstract : " Reproducibility is arguably the most important aspect of any scientific work " This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research at https://doi.org/10.1002/cctc.201901686 .